(3eSCdI aj JejjR GdaVGFd GdKdGKI GdVQhQjI hGdeecfI hGdeWdbIs - (3CHh eMeO Hf edjM GdQbGOs ((3eOjfI GdeQjI s)
(3ChdgG (B:s
(3GdZQV ai gPG Gdbhd JejjR Ufa ef GdaVGFd GdKdGKI , CYfi GdVQhQjI hGdeecfI hGdeWdbI s
(3BNQgG (B:s
(3hEf cGfJ ajgG VQhQjI HhLg eG agh ef bHjd Gdeecf , Ydi eG PcQfGg bHd , hGddg CYde SHMGfg , cedJ GdebGdI , hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3hgj ef cJH CejQ GdeDefjf RjOGf GdMSfis
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(632/5) s
Keywords: (3GdadSaI hGdefWbs